Panel Data Regression Analysis of Socio-Economic Factors on the Human Development Index in Regencies/Cities - Aneska Denadah; Bernadhita Herindri Samodera Utami; Edwin Russel; Khoirin Nisa (Jurnal Varian, 2026)
The Human Development Index (HDI) is an important indicator for assessing the success of human development; however, disparities in HDI persist across regencies and cities in Lampung Province. This study aims to examine the effects of Gross Regional Domestic Product (GRDP), poverty rate, and average years of schooling on HDI using panel data from 15 regencies/cities during 2019–2024. Average years of schooling is one of the constituent indicators used to calculate HDI. Therefore, its estimated effect should be interpreted as an empirical association rather than an independent causal determinant of HDI. Panel data regression was employed using the Fixed Effect Model (FEM) estimated by the Least Squares Dummy Variable (LSDV) approach. The estimation results show that a 1% increase in average years of schooling is associated with a 0.1208% increase in HDI (β = 0.1208, p − value = 0.0109). Meanwhile, GRDP (β = −0.0548, p − value = 0.2074) and the poverty rate (β = 0.0264, p − value = 0.2587) do not have statistically significant effects on HDI. These findings indicate that educational attainment plays a more important role than the other socio-economic variables considered in explaining HDI disparities across regencies and cities in Lampung Province.